Pengakuan Pembiayaan Mudharabah dalam PSAK 105: Kajian Maslahah Mursalah - Rizki Ameliyani; Mustafa Zulhas'ari; Musyahid Ahmad; M. Jamaluddin; Wawo Andi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The growth of Islamic financial institutions in Indonesia continues to progress, yet the implementation of profit-sharing contracts such as mudharabah remains limited when compared to consumptive financing models. This situation raises questions regarding the relevance and application of accounting standards governing mudharabah transactions, particularly PSAK 105. This study aims to analyze the accounting recognition of mudharabah under PSAK 105 and evaluate its alignment with Maslahah Mursalah as a contemporary Islamic legal approach. A qualitative library research method was employed by reviewing PSAK 105 and related academic literature. The results indicate that the recognition of investment, profit-sharing, losses, impairment, and receivables after contract termination reflects principles of public interest, fairness, transparency, and wealth protection (?if? al-m?l). The discussion shows that PSAK 105 is consistent with maq??id al-shar?‘ah and does not contradict Islamic sources. The implication of this study is that PSAK 105 serves not only as a technical accounting standard but also as a regulatory framework that strengthens governance, public trust, and the practice of Islamic economics.